Institutionality of gender in the state : new analytical perspectives - Guzmán, Virginia (ECLAC SantiagoCL, 2001)
Examines the emergence of a new social subject, women, at the national and regional levels. Focuses on the process whereby the institutionality of gender came to form part of the institutional agendas of the United Nations and the governments in the region. Considers the current debates on the role of the state and clarifies the various social, political, institutional and symbolic determinants that facilitate or hamper the inclusion and institutionalization of gender in public policies.